Click and photo-release dual-functional nucleic acid nanostructures. Issue 65 (29th July 2019) - Valsangkar, Vibhav A.; Chandrasekaran, Arun Richard; Zhuo, Lifeng; Mao, Song; Lee, Goh Woon; Kizer, Megan; Wang, Xing; Halvorsen, Ken; Sheng, Jia
Abstract : DNA nanostructures are useful in drug delivery, with cargos attached via click chemistry and released using light-based triggers. Abstract : We functionalize nucleic acid nanostructures with click chemistry (for attachment of cargos) and a photocleavable linker (for release). We demonstrate cargo attachment using a fluorescein dye and release using UV trigger from an RNA three-way junction, a DNA star motif and a DNA tetrahedron. Such multifunctional nucleic acid nanostructures have potential in targeted drug delivery.